Pengaruh Laju Aliran Bahan Bakar CNG pada Performa Mesin Kendaraan Bermotor - Ridwan Arief Subekti (Balai Besar Bahan dan Barang Teknik, 2016)
This paper discusses the influence of CNG flow rate on the performance of the minibus four-wheel vehicle. Tuning and testing were done to look for the best CNG flow rate to get optimal vehicle performance. The first phase from this study is installation of sequential injection converter kit in the vehicle. Furthermore, examination at dynotest is then conducted to obtain vehicle performance. In the beginning, fuel used is Pertamax RON 92, which was then replaced with CNG. The test of two fuels indicated that the power and torque of vehicles decreased when using CNG. The next phase was CNG flow rate setting by adjusting the duration of injector spraying. The test results were presented the form of graphs